Takotsubo is not a cardiomyopathy. (1st March 2018) - Pelliccia, Francesco; Sinagra, Gianfranco; Elliott, Perry; Parodi, Guido; Basso, Cristina; Camici, Paolo G.
Abstract: Unraveling the mechanisms underlying Takotsubo (TTS) leads to question the current inclusion of the condition within the spectrum of cardiomyopathies. Indeed, the clinical presentation and pathophysiology of TTS clearly differ from cardiomyopathies, i.e. diseases of heart muscle unexplained by abnormal loading conditions or coronary artery disease, which cannot recover spontaneously and may cause sudden death often in minimally symptomatic individuals or result in a gradual deterioration in ventricular function and end-stage heart failure. Furthermore, the term 'cardiomyopathy' can no longer be applied when functional or morphologic abnormalities of the coronary arteries leading to acute myocardial ischemia are deemed responsible for left ventricular (LV) systolic dysfunction. After 27 years of investigation, time has come to recognize that patients with TTS do suffer from severe myocardial ischemia and fulfill all criteria of acute coronary syndromes, i.e. acute chest pain, typical electrocardiographic changes, cardiac troponin rise, as well as LV wall motion abnormalities. Accordingly, we propose that TTS should be labeled as an acute 'syndrome' to be included more appropriately within the spectrum of ischemic heart disease. With regard to the term 'stress', it may imply that the catecholamine surge is essential to produce the typical transient myocardial injury. Thus, the terminology 'Takotsubo (stress) syndrome' would more accurately reflect recent advances in the pathophysiology. Highlights: The current inclusion of Takotsubo syndrome within the spectrum of cardiomyopathies should be questioned The term 'cardiomyopathy' can no longer be applied when functional or morphologic coronary abnormalities occur Clinical presentation and pathophysiology of Takotsubo syndrome clearly differ from cardiomyopathies Patients with Takotsubo syndrome suffer from myocardial ischemia and fulfill all criteria of acute coronary syndromes Takotsubo syndrome should be included more appropriately within the spectrum of ischemic heart disease